Perfusion mode as a factor of appearance of cognitive dysfunction in patients after on-pump coronary artery bypass grafting - S.M. Sudakevych; О.А. Loskutov; І.P. Shlapak; V.V. Babenko; B.М. Todurov (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate the effect of perfusion pressure during cardiopulmonary bypass on the occurrence of postoperative cognitive dysfunction in patients undergoing coronary artery bypass grafting (CABG) with cardiopulmonary bypass (CPB). Маterials and methods. In a retrospective observational one-center study, data from clinical and instrumental examination of 71 patients selected for surgical intervention for coronary heart disease – on-pump CABG (57 (80.2 %) males and 14 (19.8 % ) of women with an average age of 58.7 ± 7.7 years), were analyzed. All patients included in the study were divided into 2 groups depending on the mode of perfusion, namely, the values ​​of blood pressure maintained during the CPB. Group 1 included patients who had a perfusion pressure maintained at a level of 40–60 mm Hg during the CPB, group 2 – more than 60 mm Hg. During CPB. Neurocognitive and psychometric tests in both groups were performed prior to surgery, on day 7, and also 3 months after the operation. The test battery consisted of a Mini Mental State Examination, a Grooved Pagboard and a Trial Making Test Part A. Results. The results of the Trial Making Test Part A tests showed that patients of the 1st group were spending 21.6 (18.4, 32.1) % more time for testing (as compared to the initial time) on day 7 and by 7.9 (5.3, 15.6) % more time in 3 months at that time, as in the second group, this indicator was 13.8 (11, 16.5) % on day 7 and 3.3 (0, 5.7) % after 3 months. The result of the MMSE test demonstrated that patients in the 1st group had 11.5 (–18.5, –6.9) % less points compared with the initial level on the 7th day after the intervention and 9.9 (–4.2, 8.7) % less than 3 months after the operation. At the same time, patients in the 2nd group accrued respectively 7.8 (–14.2, –5.6) %, 3.8 (–7.3, –3.4) % less points on the 7th day and 3 months after the operation. The results of the Grooved Pegboard test showed that patients of the 1st group spent 13.3 (8.2, 24.1) % more time on the 7th day after surgery and 6.3 (3.2, 10.8) % more time 3 months after surgery. At the same time, the indicators of patients in the 2nd group amounted 8 (5.5, 10.9) % and 4.8 (2.5, 9.4) %, respectively, 7th day and 3 months after the operation. Conclusions. The support of optimal parameters of perfusion pressure during artificial blood circulation in patients undergoing coronary artery bypass grafting, namely maintaining it at a level above 60 mm Hg, is an extremely important criterion and it can reduce the incidence of postoperative cognitive dysfunction in the early postoperative period and 3 months after surgery. Use of perfusion mode with the support of average perfusion pressure less than 60 mm Hg is a factor in the occurrence of postoperative cognitive dysfunction.